The application of statistical methodology to the analysis of time-resolved X-ray diffraction data - Burley, J; O'Hare, D; Williams, G (2011)
We demonstrate for the first time the application of Principal Component Analysis (PCA) to the analysis of time-resolved energy-dispersive X-ray diffraction data. Previously well-characterised model systems are studied. PCA is shown to offer significant advantages over traditional curve-fitting methods in terms of speed and lack of potential user bias. © 2011 The Royal Society of Chemistry.